Paraneoplastic thrombocytosis independently predicts poor prognosis in patients with locally advanced pancreatic cancer. (July 2015) - Chadha, Awalpreet S.; Kocak-Uzel, Esengul; Das, Prajnan; Minsky, Bruce D.; Delclos, Marc E.; Mahmood, Usama; Guha, Sushovan; Ahmad, Mediha; Varadhachary, Gauri R.; Javle, Milind; Katz, Matthew H.; Fleming, Jason B.; et al.
Abstract Background and aims. Platelets are believed to promote tumor growth and metastasis but their prognostic role in locally advanced pancreatic cancer (LAPC) remains largely unknown. We assessed whether pretreatment platelet counts independently predict survival outcomes in patients with LAPC treated with chemoradiation (CRT). Methods. We retrospectively reviewed the MD Anderson pancreatic cancer database and identified 199 patients with LAPC treated with CRT between 2006 and 2012. Induction chemotherapy was used prior to consolidative CRT in 177 (89%) patients. Median radiation dose was 50.4 Gy. Concurrent radiosensitizers were gemcitabine-based (13%) or capecitabine-based (84%) regimens. Actuarial univariate and multivariate statistical methods were used to determine significant prognostic factors for overall survival (OS) and progression-free survival (PFS) calculated from the start of treatment. Results. Median follow-up was 9.9 months. Median OS and PFS durations were 17.7 and 10.7 months, respectively. On univariate analysis, platelet count > 300 K/μl, KPS ≤ 80, ≥ 5% weight loss and pretreatment CA19-9 above the median were associated with inferior OS or PFS. Median OS was lower in patients with platelet count > 300 K/μl compared to patients with platelet count ≤ 300 K/μl (10.2 vs. 19 months; p = 0.0002). Corresponding median PFS times were 7.8 months and 11.1 months (p = 0.004), respectively. On multivariate analysis, platelet count > 300 K/μl (p = 0.012), ≥ 5% weight loss (p = 0.002) and elevated pretreatment CA19-9 (p = 0.005) were independent prognostic factors for OS. Platelet count > 300 K/μl (p = 0.03) and KPS ≤ 80 (p = 0.05) independently predicted PFS. Conclusions. Our analysis suggests that pretreatment thrombocytosis independently predicts inferior OS and PFS in LAPC.